Modelling of mechanical systems. - Axisa, Francois, 1941- (Kogan Page Science, 2007)
Written by an eminent authority in the field, Modelling of Mechanical Systems: Fluid-Structure Interaction is the third in a series of four self-contained volumes suitable for practitioners, academics and students alike in engineering, physical sciences and applied mechanics. The series skilfully weaves a theoretical and pragmatic approach to modelling mechanical systems and to analysing the responses of these systems. The study of fluid-structure interactions in this third volume covers the coupled dynamics of solids and fluids, restricted to the case of oscillatory motions about a state of static equilibrium. Physical and mathematical aspects of modelling these mechanisms are described in depth and illustrated by numerous worked out exercises. Written by a world authority in the field in a clear, concise and accessible style Comprehensive coverage of mathematical techniques used to perform computer-based analytical studies and numerical simulations A key reference for mechanical engineers, researchers and graduate students.